INCREASING AWARENESS AND READERSHIP OF TRIBUN JAWA TENGAH NEWSPAPER AS COMMUNICATION MANAGER - Windariani Soeryo Handadari; Djoko Setyabudi, S.Sos, MM (Interaksi Online, 2016)
Tribun Jawa Tengah is a brand of newspaper which is a subsidiary of Kompas Gramedia Group. Established on January 17, 2011, Tribun Jateng has a early name Warta Jawa Tengah, and then turns into Tribun Jawa Tengah on 29 April 2013. Tribun Jawa Tengah has a vision to be the group's largest regional media publishing business, spread and leading in Central Java with the slogan "New Spirit of Java Central ". With the slogan and the vision, Tribun Jawa Tengah keep trying to increase awareness and readership Central Java society. This karya bidang is departing from desire of Tribun Jawa Tengah that want to expand its targets to young people aged 18-25 years and introducing Tribun Jawa Tengah on new distribution areas. Based on preliminary data owned by Tribun Jawa Tengah awareness and readership of target is still low. This is reinforced by the survey data that awareness and readership Tribun Jawa Tengah still low in amongs the target. Semarang Youth Community is an event that designed for young people by involving the community and music artists in Semarang. The purpose of Semarang Youth Community is to raise awareness and readership at young people aged 18-25 years. Jalan Sehat Tribun Jateng Melangkah bersama Paramex is an event held in Grobogan disctrict and is designed for the general public of all ages and backgrounds. The purpose of the event Jalan Sehat Tribun Jateng Melangkah bersama Paramex is to increase awareness and readership of Grobogan district residents about Tribun Jawa Tengah remember just reopen his newspaper's distribution area in this region. The results achieved from Semarang Youth Community 2016 event is increasing awareness in young adult from 71% to 91% and a readership from 52% to 82%. While the results of Jalan Sehat Tribun Jateng Melangkah bersama Paramex in Grobogan district is increasing awareness from 44% to 69% and a readership from 10% to 26% and increasing circulation from 400 copies to 600 copies per day. Communication Manager task in both events is to establish cooperation with other parties such as community, local government, media, and ticketbox, as well as take care of all matters relating to the publication of an event such as the creation of content publishing and monitoring publications.